A community approach to the Neotropical ticks-hosts interactions - Estrada-Peña, Agustín; Nava Santiago; Tarragona Evelina Luisa; de la Fuente, José; Guglielmone Alberto (Springer Nature, 2020)
The relationships between ticks and hosts are relevant to capture the ecological background driving the evolution of these parasites. We used a set of 4,764 records of ticks of the genera Amblyomma, Ixodes, and Haemaphysalis and their hosts in the Neotropics to approach the tick-host relationships using a network-based construct. The network identified 9 clusters of interacting hosts and ticks partially connected by 22 tick species that switch their host range according to their life cycle stage. These links among clusters do not confer an extra resilience to the network following removal of hosts and subsequent cascade extinctions of ticks: the robustness of the network slightly changed when these inter-clusters links are considered. Phylogenetic clustering of ticks to hosts at cluster level was not significant (p > 0.15) but if examined individually 63 tick species/stages (59%) displayed such clustering, suggesting that their hosts have a related phylogenetic background. We interpreted these results under an ecological perspective in which ticks could track its environmental niche associating to vertebrates that would maximize tick survival under the range of abiotic traits. We encourage these integrated analyses to capture the patterns of circulation of tick-transmitted pathogens, a topic still unaddressed in the Neotropical region.